USER SATISFACTION ANALYSIS OF SIDIA UNESA BASED ON PERCEIVED USEFULNESS, SYSTEM, INFORMATION, AND SERVICE QUALITY - Mukhtarul Fata An Nadwi; I Kadek Dwi Nuryana (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2025)
SIDIA UNESA (Sinau Digital UNESA) is an information system that supports lectures and administration at Surabaya State University. The purpose of this study was to determine the effect of perceived usefulness, system quality, information quality, and service quality variables on user satisfaction of the SIDIA UNESA system. A preliminary survey of several Surabaya State University students revealed that they were not fully satisfied with the services provided by SIDIA UNESA because several obstacles were often experienced by students. The research used quantitative methods with an associative descriptive approach. The analysis method used is Structural Equation Modeling (SEM) with the help of the SmartPLS application. The population in this study were UNESA students who were actively studying, with a sample size of 115 respondents. The findings revealed that the variables of perceived usefulness, system quality, information quality, and service quality positively impact user satisfaction with the UNESA SIDIA system. Additionally, the variables of perceived usefulness, system quality, information quality, and service quality simultaneously impact user satisfaction with the UNESA SIDIA system.